Pengaruh Penyuluhan dengan Metoda Demontrasi Terhadap Peningkatan Pengetahuan dan Tindakan Pengelolaan Sampah Ibu-Ibu di Desa Cetan, Kecamatan Ceper, Kabupaten Klaten Tahun 2014 - Sri Pangesti Dewi; Lucky Herawati; Sri Puji Ganefati (Poltekkes Kemenkes Yogyakarta, 2015)
Knowledge and practice about waste management among housewives in Cetan Village were low, i.e. 40 % did not know about waste and the health impact from bad waste management, and 65,6 % knew that waste can only be managed by burning it and throwing onto yards and rivers, 78 % had behavior of mixing and burning organic and inorganic wastes, and 22 % had habituality of throwing the mixed wastes onto vacant yards and rivers. This study was aimed to know the influence of demonstration method for increasing the knowledge and practice of the housewives about domestic waste management. The research method used was quasi experiment with non-equivalent control group design. 40 respondents for the experiment group and other 40 respondents for the control group were selected by using purposive sampling method. The data was analyzed by using Anova multivariate test at 95 % confidence level. A nine itemed questionnaire which had been tested for its validity (p<0,05) and realibility (p=0,711) was administered to measure the knowledge level, meanwhile a checklist with five items was used to measured the level of practice (the corresponding validity reliability tests yielded p values of <0,05 and 0,701, respectively). The results of the research showed that, in general, the elucidationwith demonstration method influenced the increase of knowledge and practice among the housewives (p=0,037). However, in specific, only the practice aspect was observed increase significantly (p=0,017), meanwhile the knowledge aspects was not (p=0,428). It can be concluded that demonstration method is more effective for increasing the practice of housewives in domestic waste management.